11.3k views
1 vote
Solve this system of equations byusing the elimination method.-4x + y = 6–5x - 2y = -3([?], []).=

Solve this system of equations byusing the elimination method.-4x + y = 6–5x - 2y-example-1

1 Answer

4 votes

Given the system of equations:

4x + y = 6 equation 1.

–5x - 2y = -3 equation 2.

• First, we multiply eq 1; by 2:

8x + 2y = 12 equation 3.

• Now, we add eq 2 and eq 3, as follows:

–5x - 2y = -3

8x + 2y = 12

____________

3x = 9

x = 3

Finally we substitute x = 3, on eq 1:

4x + y = 6

4(3) + y = 6

12 + y = 6

y = 6 - 12

y = -6

ANSWER = [3, -6]

User Superuseroi
by
5.1k points